Investigation of New 4-Benzyloxy-2-trichloromethylquinazoline Derivatives as Plasmodium falciparum Dihydrofolate Reductase-thymidylate Synthase Inhibitors: QSAR, ADME, Drug-likeness, Toxicity, Molecular Docking and Molecular Dynamics Simulation - Yogaswara, Radite; Pranowo, Harno Dwi; Prasetyo, Niko; Pulung, Maria Ludya (Journal of Multidisciplinary Applied Natural Science, 2025)
Plasmonium falciparum dihydrofolate reductase-thymidylate synthase (PfDHFR-TS) is one of the most crucial antimalarial targets. Mutations in the binding pocket of this target lead to resistance to the antifolate. The mutations influence the amino acid residues at points 51, 59, 108 and 164 and contribute significantly to malaria not being treated well. Priority should therefore be given to the development of antifolate-resistance drugs. These studies aim to investigate new 4-benzyloxy-2-trichloromethylquinazoline derivatives as PfDHFR-TS inhibitors using QSAR, ADME, drug-likeness, toxicity, molecular docking studies, and molecular dynamics simulations. The best equation model from the QSAR analysis used MLR and PLS statistics to show that the pIC50 is linearly related to GATS4e, SpMax AEA(ed), and Mor28e, but inverted when compared to ATS6m and ATSC7m. The predictive ability of the model was confirmed by internal and external validation. In addition, the Y-randomization validation showed that the QSAR model was reliable, robust, and stable, with a cRp2 score of over 0.5. ADME and drug-likeness predictions confirmed the new QSAR design for molecules S10, S23 and S64. Based on the toxicity results, three molecules are expected to have moderate and non-toxic properties, starting with S23 and then S10 and S64. Molecular docking studies show that all three molecules have high binding energies, 9.869, 9.589, and 9.565 kcal/mol. The amino acid residues Leu46, Asp54, Ser111, and Thr185 play a major role in ligand-receptor interaction in the binding pocket of quadruple mutant PfDHFR-TS. Furthermore, an evaluation of molecular dynamics simulations of three complexes S10-3JSU, S23-3JSU and S64-3JSU demonstrated stable interactions over 100 ns.